Catalytic artificial nitroalkane oxidases – a way towards organocatalytic umpolung. Issue 13 (15th March 2023) - Pokluda, Adam; Zubova, Ekaterina; Chudoba, Josef; Krupička, Martin; Cibulka, Radek
Abstract : Artificial nitroalkane oxidases based on catalytic amounts of flavins enable nitroalkane umpolung resulting in β-nitroalcohols. Two alternative pathways via flavin-5-iminium species are possible. Abstract : Nitroalkane oxidases (NAOs) are flavoenzymes that catalyse the oxidation of nitroalkanes to their corresponding carbonyl compounds while producing nitrite anions. Herein, we present an artificial catalytic system using flavins or ethylene-bridged flavinium salts that works via an NAO-like process. Under conditions optimised in terms of solvent, base, temperature and oxygen pressure, primary nitroalkanes were transformed to aldehydes. In our system, aldehydes immediately reacted with other nitroalkane molecules to form β-nitroalcohols. The reduced flavin catalyst was re-oxidised by oxygen. An alternative mechanism towards β-nitroalcohols via 5-(2-nitrobutyl)-1, 5-dihydroflavin was suggested through quantum chemical calculations and by trapping and characterising this dihydroflavin intermediate. Interestingly, 5-(2-nitrobutyl)-1, 5-dihydroflavin is an analogue of the flavin adenine dinucleotide adduct previously observed in an NAO X-ray structure. In both mechanistic pathways, flavin-5-iminium species is formed by nitroalkanide addition to flavin. This process represents flavin-based umpolung of an original donor to an acceptor.